2021
DOI: 10.3390/genes12091433
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences Measured by Epigenetic Clock and Vulnerability Components at Birth Impact Clinical ASD Heterogeneity

Abstract: Although Autism Spectrum Disorders (ASD) is recognized as being heavily influenced by genetic factors, the role of epigenetic and environmental factors is still being established. This study aimed to identify ASD vulnerability components based on familial history and intrauterine environmental stress exposure, explore possible vulnerability subgroups, access DNA methylation age acceleration (AA) as a proxy of stress exposure during life, and evaluate the association of ASD vulnerability components and AA to ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…The second goal was to explore the contribution of psychiatric and neurological FH to ASD, as we have only analyzed psychiatric disorders in our small sample size previous study [ 23 ]. Our FH analysis considered cases of psychiatric disorders and neurological diseases, including neurodevelopmental and neurodegenerative forms in all respondents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second goal was to explore the contribution of psychiatric and neurological FH to ASD, as we have only analyzed psychiatric disorders in our small sample size previous study [ 23 ]. Our FH analysis considered cases of psychiatric disorders and neurological diseases, including neurodevelopmental and neurodegenerative forms in all respondents.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to consider that individuals, especially in developing countries, are not usually exposed to only one factor, but different correlated exposures at the same time [ 22 ]. In a previous study, with 67 ASD cases, we showed that prenatal vulnerability components and epigenetic age acceleration as a proxy of postnatal stress exposure were associated with ASD severity and functionality scores measured at 08 years of age [ 23 ]. We used psychiatric FH representing genetic vulnerability and gestational exposure to EF to search the prenatal vulnerability components using principal component analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
“…Only one investigation included in the current systematic review investigated the epigenetic clock in peripheral blood, observing that ASD children had a biological age greater than their chronological age [46]. The epigenetic clock is a relatively new method for analyzing genome-wide DNA methylation data, allowing us to evaluate an individual's biological age.…”
Section: Discussionmentioning
confidence: 99%
“…One of these, the SH2B1 gene, was chosen for further bisulfite pyrosequencing analyses in all the subjects enrolled; its methylation levels were found to increase in ASD-discordant monozygotic twins compared to concordant monozygotic and in sporadic ASD compared to control subjects [44]. In one study, methylome data obtained in the peripheral blood of 67 ASD patients by means of the 450 K array were correlated with prenatal environmental risk factors, including maternal stress and gestational complications [46]. Several DMPs were identified in children of mothers with different grades of psychological stress vulnerability, although the names of the genes were not reported.…”
Section: Main Dna Methylation Findingsmentioning
confidence: 99%
See 1 more Smart Citation